Analysis of Risk Factors Affecting Skin Mastocytosis in Children: Cross-Sectional Study - Elena I. Kasikhina; Larisa S. Kruglova; Mariya O. Vashchenko; Roman Y. Mayorov (Вопросы современной педиатрии)
Background. Skin mastocytosis is rare disease that is diagnosed in most children under the age of 2 years. The date on rash regression dynamics and disease symptoms is not fully presented in the literature.Objective. The aim of the study was to analyze risk factors associated with clinical manifestations and regression time of skin mastocytosis in children.Methods. The study includes data on 28 children aged from 3 months to 12 years who has undergone outpatient care and observation in Moscow Scientific and Research Center of Dermatovenerology and Cosmetology of Moscow City Health Department in the period between January 2016 and November 2019. The data about diagnosis was obtained from medical records.Results. Maculopapular skin mastocytosis (MPSM) was diagnosed in 28.6% of children, solitary mastocytoma — in 71.4%. The analysis of clinical course of skin mastocytosis has shown constantly relapsing process and slow spontaneous rash regression in more than 50% of children. Diffuse skin rash, flushing reactions, persistent skin itching or its combination with hepatomegaly or neurological symptoms were prevalent among MPSM manifestations. Risk factors affecting delayed regression of skin mastocytosis in children with MPSM are: late onset, area of skin lesions, comorbidities, severity of reticular vascular pattern at dermatoscopy. Severity of skin lesions did not affect the tryptase activity. The major risk factor affecting the delayed regression of solitary mastocytoma is rash injury (OR 6.10, 95% CI 3.66–16.73). The severity of reticular vascular pattern in skin mastocytosis foci has varied depending on the severity of skin lesions.Conclusion. Half of all children with skin forms of mastocytosis have delayed rash regression. This causes high concern among parents and violates social adaptation of children. Timely assessment of risk factors alongside with dynamic assessment of the dermatoscopy patterns and tryptase activity are important for implementation of correct follow-up monitoring and management for children. Rash (of any localization) injuries should be avoided to prevent delayed regression of the disease in children with skin forms of mastocytosis.